Una nueva especie de serpiente venenosa terrestre del género Porthidium (Serpentes: Viperidae), del Suroeste de Costa Rica - Solórzano, Alejandro (1994)
A new species of terrestrial pitviper, Porthidium volcanicum, is described from low elevations near Buenos Aires, in the Valle del General, southwestem Puntarenas Province, Costa Rica. It is the eighth known member of the hognosed pitviper genus. Distinctive characters are the color pattem, high number of dorsal blotches and ventral scales, together with the presence of a single canthal scale. These morphological data indicate close affinities with Porthidium lansbergii